Dziela poetyckie - Mickiewicz, Adam, 1798-1855. (Warszawa : Czytelnik, 1992)
The poetical works of the famous 19th century Polish poet.
t. 1. Wiersze -- t. 2. Powiesci poetyckie. Ksiegi narodu polskiego i pielgrzymstwa polskiego -- t. 3. Dziady -- t. 4. Pan Tadeusz.